Childhood vaccination trends among the Maasai nomadic pastoralists: Insights from a community-based vaccine registry in Kenya. - Julius Nyerere Odhiambo; Carrie B Dolan; Evelyn Thompson; Katie O'Neill; John Sankok; Rose Kimani (PLOS Global Public Health)
Inequities in vaccination timeliness and coverage contribute to disparities in childhood health and survival. Regular, reliable estimates are needed to take programmatic action and track progress towards initiatives such as the Immunization Agenda 2030. This study assessed the timeliness, coverage, and drop-out rates of reported immunization data from a community healthcare registry. We retrospectively reviewed vaccination records of 8487 children across 176 villages. The proportion of children receiving early, timely and delayed vaccination was computed by vaccine, village and year. Coverage of each vaccine was calculated as the number of reported doses divided by the number of children who received Bacillus Calmette-Guerin (BCG), a birth dose serving as the service-based denominator. Vaccine dropout by year was estimated as the proportion of children who received the first dose of a vaccine but did not receive the subsequent dose. For multi-dose vaccines, on-time vaccination rates were highest for the first dose but declined with subsequent doses. The largest declines between the first and third doses were observed in DPT (29.07%), Pneumococcal Conjugate Vaccine (28.84%), and Oral Polio Vaccine (28.79%). The Measles-Rubella vaccine had the highest dropout rate (64.66%) between its two doses, largely due to delays in administering the second dose at 18 months. Overall, vaccination coverage steadily declined from mid-2020 to 2022, with proximity to healthcare facilities strongly linked to higher coverage and lower dropout rates. The study confirmed that community level estimates were significantly below the national immunization targets. Understanding factors affecting coverage, timeliness and dropout rates at this level is important for building a strong and sustainable vaccine ecosystem for hard-to-reach communities.